Implementasi penggunaan media pembelajaran interaktif berbasis digital terhadap hasil belajar IPA pada materi peredaran darah manusia - wilis eka sulistyorini; Arif Widyatmoko; Langlang Handayani (Universitas Sebelas Maret, 2025)
This study aims to examine the impact of digital-based interactive learning media on students’ learning outcomes in the topic of the human circulatory system in grade five of elementary school. A systematic literature review approach was used, analyzing studies published between 2020 and 2025. The findings reveal that interactive media—such as animations, videos, and digital simulations—significantly enhance students’ conceptual understanding, foster active learning motivation, and make science lessons more engaging and easier to comprehend. These media tools effectively address challenges in teaching abstract scientific concepts that are not easily observable. With visually appealing and interactive features, digital media offers a student-centered learning experience aligned with the Merdeka Curriculum. The results highlight the value of technological innovation in science education and provide useful insights for educators, media developers, and educational researchers.